Mandatory patient surveys and hospital resource allocation - Capkun, Vedran; Cianciaruso, Davide; Sinha, Kirti (Review of Accounting Studies, 2026)
We study whether mandatory surveys of patient experience affects patient mortality in U.S. hospitals. We exploit two settings where healthcare regulators mandated the Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) survey: the 2003 Maryland pilot study and the 2007 nationwide adoption. Difference-indifferences analyses show increased mortality for hospitals that were subject to the mandate, relative to other comparable hospitals. We observe this effect before hospitals disclose their HCAHPS ratings, which suggests that it is attributable to measurement, rather than to disclosure. An analysis of changes in hospital expenses shows that, after the mandate, affected hospitals experienced a relative increase (decrease) in non-clinical (clinical) expenses. This finding is consistent with theories of multitasking, which predict that more incentives for one task (in this case, patient experience) cause some reallocation of resources from other tasks (clinical care).